Twain's end [large type] - Cullen, Lynn (Wheeler Publishing, 2016)
In March of 1909, Mark Twain cheerfully blessed the wedding of his private secretary, Isabel V. Lyon, and his business manager, Ralph Ashcroft. One month later, he fired both and wrote a 429-page rant calling Isabel "a liar, a forger, a thief, a hypocrite, a drunkard, a sneak, a humbug, a traitor, a conspirator, a filthy-minded and salacious slut pining for seduction." In Twain's End, Lynn Cullen reimagines the tangled relationships that transformed Isabel Lyon from beloved secretary into a woman Twain was determined to destroy.